(untitled) (Medical Forum Monthly, 2021)
Objective: The purpose of this study was to compare the efficacy of Bipolar Diathermy with Ligation techniques in hemostasis, the duration of operation, postoperative pain and incidence and severity of postoperative reactionary hemorrhage. Study Design: A Prospective Comparative Study Place and Duration of Study: This study was conducted at the Sughra Shafi Medical Complex, Narowal from June 2018 to December 2020. Materials and Methods: 98 patients with chronic tonsillitis were included and randomly assigned two groups A and B. 49 patients of group A underwent conventional tonsillectomy under general anesthesia and hemostasis was achieved by Ligation of vessels with 1/0 silk and in 49 patients of group B Bipolar Diathermy was used for hemostasis. The duration of surgery, incidence and severity of Postoperative hemorrhage, severity of post-operative pain was recorded during the stay in the ward and at weekly follow ups for two weeks. Results: The duration of operation in group B was much less as compare group A. The overall incidence of postoperative haemorrhage was 10.2% with no significant difference in the two groups. The incidence of postoperative pain was recorded in the ward and follow up. Statistically, the difference was not significant with a slight preponderance of pain in group A Conclusion: Both techniques are equally effective in hemostasis. The bipolar diathermy technique is faster, resulting in saving the time of surgeon and anesthetist and also cost-effective. It is also found to be less painful to the patient on follow ups.